Dinamika Perilaku Kecurangan Akademik Pada Siswa Sekolah Berbasis Agama - Purnamawati, Sari; , Dr. Sri Lestari, M.Si (2016)
The study describes the dynamyc of academic fraud of the religion based school students which consist of four factors: (1)self, (2)friends, (3)teachers, and (4)parents. The study took place in MAN Al Huda Semarang District involving five students. The data is collected by interview and then analyzed by using interactive model. Based on the result of the study, it can be concluded that: (1) the self factor, informant do academic fraud because: (a) their view towards frauds behavior, (b) the laziness or low motivation, (c) difficulty in understanding the materials, and (d) the need of acknowledgement or recognition. (2) the friends factor consists of: (a) the influence of friends' behavior, (b) solidarity or conformity, (c) cooperation. (3) the teachers factor consists of: (a) the surveillance in the examination, (b) the method and condition of the learning process, and (c) teachers' discipline. (4)the parents factor consists of:(a) the demand of high score, (b) lack of attention, (c) the attitude of comparing. The dynamic of academic fraud of the religion based school students can be concluded as follows: (1) informants have positive view towards cheating which makes them continuously do the act, (2) informants believe that cheating and cooperating with friends is advantageous act that can give them good scores and so the act is become a habit. (3) the method and condition of the learning process encourage the informants to repeatedly do the cheating act, and (4) the parents' demand of high scores without giving attention force the informants do the fraud